Analysis of the preferences of young adults regarding touristic destinations - Martins, Miguel Celestino Marques (2013)
The Portuguese economy has been struggling for the last decade. However, Portuguese tourism is rising due to the growth of external demand. Thus, it is very important to be aware of the strengths and weaknesses of the Portuguese touristic sector once it is helping Portugal’s economy. This study analyses the preferences of young adults for travel destinations. More specifically, those preferences are explained based on different variables such as the travellers’ awareness, the personality and image of competing travel destinations, the tourists’ motivations regarding types of vacations and also the demographic characteristics. Both qualitative and quantitative research was conducted to address those issues. The results suggest that the greater the awareness people have about a country, the more likely is that they will prefer to visit it. However, Portugal has a low awareness among young adults and as a consequence it is less likely to attract them. Additionally, the results also suggest that if the destination personality is “Adventurous” or its image is “Friendly” then there will be higher likelihood that young adults will visit that destination. Nevertheless, Portugal is perceived to have a “Family Oriented” personality which makes it harder to attract young adults. Moreover, an interesting result obtained was the fact that Portugal was the only country whose likelihood of visiting decreases if the respondents are Asians. Nonetheless, Portugal was also the only destination whose likelihood of visiting increases for individuals who have previously visited the country.